CD8(+) T Cells Participate in the Memory Immune Response to Mycobacterium tuberculosis - Serbina, Natalya V. (American Society for Microbiology, 2001)
The contribution of CD8(+) T cells to the control of tuberculosis has been studied primarily during acute infection in mouse models. Memory or recall responses in tuberculosis are less well characterized, particularly with respect to the CD8 T-cell subset. In fact, there are published reports that CD8(+) T cells do not participate in the memory immune response to Mycobacterium tuberculosis. We examined the CD8(+) T-cell memory and local recall response to M. tuberculosis. To establish a memory immunity model, C57BL/6 mice were infected with M. tuberculosis, followed by treatment with anti-mycobacterial drugs and prolonged rest. The lungs of memory immune mice contained CD4(+) and CD8(+) T cells with the cell surface phenotype characteristic of memory cells (CD69(low) CD25(low) CD44(high)). At 1 week postchallenge with M. tuberculosis via aerosol, ≥30% of both CD4(+) and CD8(+) T cells in the lungs of immune mice expressed the activation marker CD69 and could be restimulated to produce gamma interferon (IFN-γ). In contrast, <6% of T cells in the lungs of naive challenged mice were CD69(+) at 1 week postchallenge, and IFN-γ production was not observed at this time point. CD8(+) T cells from the lungs of both naive and memory mice after challenge were cytotoxic toward M. tuberculosis-infected macrophages. Our data indicate that memory and recall immunity to M. tuberculosis is comprised of both CD4(+) and CD8(+) T lymphocytes and that there is a rapid response of both subsets in the lungs following challenge.